2021
DOI: 10.3390/s21248507
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Computer Aided Diagnosis of Acute Brain Stroke

Abstract: Amongst the most common causes of death globally, stroke is one of top three affecting over 100 million people worldwide annually. There are two classes of stroke, namely ischemic stroke (due to impairment of blood supply, accounting for ~70% of all strokes) and hemorrhagic stroke (due to bleeding), both of which can result, if untreated, in permanently damaged brain tissue. The discovery that the affected brain tissue (i.e., ‘ischemic penumbra’) can be salvaged from permanent damage and the bourgeoning growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 170 publications
(159 reference statements)
0
18
0
Order By: Relevance
“…In this section, the paper search is done based on the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines (Inamdar et al, 2021). The published papers search is performed between years 2016 and 2022 in the field of sleep apnea detection, where the general keywords like apnea, central sleep apnea, obstructive sleep apnea, and mixed sleep apnea, EOG, SpO2, EMG, ECG, EEG, PSG, respiration signals, Deep Learning, and Machine Learning have been used.…”
Section: Search Strategymentioning
confidence: 99%
“…In this section, the paper search is done based on the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines (Inamdar et al, 2021). The published papers search is performed between years 2016 and 2022 in the field of sleep apnea detection, where the general keywords like apnea, central sleep apnea, obstructive sleep apnea, and mixed sleep apnea, EOG, SpO2, EMG, ECG, EEG, PSG, respiration signals, Deep Learning, and Machine Learning have been used.…”
Section: Search Strategymentioning
confidence: 99%
“…With the advancement of medical imaging technology and the enhancement of clinical diagnosis precision, DL-based clinical diagnosis approaches have been intensively developed. A DL-based brain CT image processing system was introduced to achieve automatic identification of acute neurological events such as stroke (24,25). Zhu et al suggested an automatic diagnosis approach for ischemic stroke based on DL, with a sensitivity of 76.9%, a specificity of 84.0%, and an accuracy of 80.5%, which can offer doctors with acute ischemic stroke (26).…”
Section: Diagnostics Of Medical Conditionsmentioning
confidence: 99%
“…AI works on large datasets to detect useful patterns that helps in decision-making in disease diagnosis and hence treatment. Machine learning algorithms have been applied successfully for detecting and predicting hemorrhage stroke in NCCT brains [ 4 7 ]. Conventional image analysis techniques such as fuzzy C -means [ 8 ], level set [ 9 , 10 ], histogram analysis [ 11 ], region growing [ 12 ], thresholding [ 13 ], neural network [ 14 ], and random forest [ 15 ] have been used to successfully segment the brain hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…In the thresholding technique, the hemorrhagic lesion is segmented into a region based on threshold of each pixel. Inamdar et al [ 7 ] presented a clustering algorithm using fuzzy C -mean and active contour methods to detect the brain hemorrhages. A fuzzy membership degree has been used to control the propagation parameters and to initialize the active contour of the desired object.…”
Section: Introductionmentioning
confidence: 99%